(3efgGL GdHjGf ajeG jSJYedg GdGfSGfs - (3jMji Hf YjSi Hf LRdI GdHZOGOj, CHh Ydj,J (B493 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPj XgQJ HOGFY eUfhYGJg hHgQJ ZQGFH eHJOYGJg GdcJGH GdPj SejJg HJbhje GdGHOGf HGOQJ JQJjH cJGH SejJg efgGL QHjGf aVefg PcQ LejY GdGOhjI hGdGTQHI hGdGZPjI hcd eQcH s
(3BNQgG (B:s
(3jfJhf gh GdJGajSjG Cj UeZ GdSPGH GdLHdj BNQ cJGH efgGL GdHjGf s
(3fbdJ Yf fSNI bQFJ Ydi gHI Gddg Hf UGYO SfI (B553 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B161 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B218s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3eJaQbGJs